2017
DOI: 10.1111/micc.12416
|View full text |Cite
|
Sign up to set email alerts
|

Acute simvastatin treatment restores cerebral functional capillary density and attenuates angiotensin II‐induced microcirculatory changes in a model of primary hypertension

Abstract: The antihypertensive effect of SIM is associated with an improvement in cerebral microvascular perfusion and capillary density that may help to prevent hypertension-induced cerebrovascular damage independent of cholesterol-lowering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 88 publications
2
23
0
Order By: Relevance
“…On the other hand, measuring LSCI perfusion is easy, noninvasive, and can be measured several times for long-term follow-up, even in small animal models such as mouse. LSCI has been used to determine microcirculation in several tissues such as in bowel lesions in neonates (Knudsen et al 2017), in brain to determine cerebral blood flow (Freitas et al 2017), in renal cortical perfusion (Mitrou et al 2016), retinal and skin perfusion (Senarathna et al 2013). Our immunostaining findings confirm endothelial dysfunction and fibrosis in the aging mouse penis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…On the other hand, measuring LSCI perfusion is easy, noninvasive, and can be measured several times for long-term follow-up, even in small animal models such as mouse. LSCI has been used to determine microcirculation in several tissues such as in bowel lesions in neonates (Knudsen et al 2017), in brain to determine cerebral blood flow (Freitas et al 2017), in renal cortical perfusion (Mitrou et al 2016), retinal and skin perfusion (Senarathna et al 2013). Our immunostaining findings confirm endothelial dysfunction and fibrosis in the aging mouse penis.…”
Section: Discussionsupporting
confidence: 64%
“…), in brain to determine cerebral blood flow (Freitas et al. ), in renal cortical perfusion(Mitrou et al. ), retinal and skin perfusion (Senarathna et al.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that in addition to hypertension treatment, hypolipidemic medications and statins in particular seem to have a beneficial effect on microcirculation even during acute administration; this is recognized as an additional pleiotropic effect of statins.…”
Section: Effects Of Antihypertensive Treatment On Microvascular Dysfumentioning
confidence: 99%
“…Intervention Summary of main findings Boegehold 28 Dahl salt-sensitive rats High-or low-salt diets for 4 wk High-salt intake reduced the passive diameter of large arterioles by 20% and was associated with increased tone of proximal, but not distal, arterioles It should be mentioned that in addition to hypertension treatment, hypolipidemic medications and statins in particular seem to have a beneficial effect on microcirculation even during acute administration 48 ; this is recognized as an additional pleiotropic effect of statins.…”
Section: Animal Modelmentioning
confidence: 99%
“…Genetic and pharmacological approaches have demonstrated that angiotensin II can trigger vasoconstriction or vasodilation via AT1 receptors or dilation through AT2 receptors located in the endothelium and smooth muscle cells of cerebral microvessels (Haberl et al 1990;Meng and Busija 1993;Baranov and Armstead 2005;Vincent et al 2005;Wackenfors et al 2006;Zhou et al 2006;De Silva and Faraci 2012;Freitas et al 2017). Human brain pericytes also express both the AT1 and AT2 receptors (Kuroda et al 2014;Fig.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%